2014
DOI: 10.1098/rsif.2014.0022
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial repair process and its relevance to longitudinal neointimal tissue patterns: comparing histology with in silico modelling

Abstract: Re-establishing a functional endothelium following endovascular treatment is an important factor in arresting neointimal proliferation. In this study, both histology (in vivo) and computational simulations (in silico) are used to evaluate neointimal growth patterns within coronary arteries along the axial direction of the stent. Comparison of the growth configurations in vivo and in silico was undertaken to identify candidate mechanisms for endothelial repair. Stent, lumen and neointimal areas were measured fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…At each step of the model, each endothelium-free SMC becomes covered by functional endothelium with a time-varying probability calculated to achieve a certain coverage scenario. 29 Figure 1c shows the model state after some growth. In this example, to the left of the top strut, the endothelium has recovered quickly and proliferation has nearly stopped.…”
Section: The Isr Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…At each step of the model, each endothelium-free SMC becomes covered by functional endothelium with a time-varying probability calculated to achieve a certain coverage scenario. 29 Figure 1c shows the model state after some growth. In this example, to the left of the top strut, the endothelium has recovered quickly and proliferation has nearly stopped.…”
Section: The Isr Modelmentioning
confidence: 99%
“…5,31 Epistemic Uncertainty in the Model For our uncertainty quantification and sensitivity analysis of the ISR2D model, we consider the uncertainty in three input parameters (Table 1). Stent deployment depth and endothelium regeneration time were shown to strongly affect simulated neointimal area by Tahir et al, 29 and were therefore included. Additionally, we included blood flow velocity, because its effect on the behavior of the model has not yet been evaluated, and because of the potentially interesting interaction with the endothelium regeneration time.…”
Section: Aleatory Uncertainty In the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As endothelium is usually damaged or dysfunctional during the early days, shear stresses occurring from the blood flow are particularly important during the middle and later phases of ISR progression, where they mitigate ISR growth [22][23][24]. The effect of flow shear stresses on the growth and tissue morphology of ISR afflicted vessel walls has already been highlighted in our previous studies using coupled ISR models [10,16]. However, the early phases of ISR that we focus on here seem to be mainly dependent on the extent of injury to the vascular wall [3].…”
Section: Computational Model Of In-stent Restenosismentioning
confidence: 92%
“…Another experimental study investigating the origin of ECs in the healed region post-stenting revealed that these cells proliferated from healthy endothelium proximal and distal to the stent, and originated from bone marrow derived cells [35]. A computational study by Tahir et al [36] modelled two mechanisms of reendothelialisation; growth from proximal and distal ends and random seeding in the denuded region. Results from these simulations showed that different patterns of neointimal growth and area are predicted by these two mechanisms.…”
Section: Figure 10mentioning
confidence: 99%